ALLERGIC REACTIONS WITH SKIN PRICK TEST AND INTRADERMAL TEST FROM THE ANTI COVID 19 VACCINES AT PATIENTS WITH HIGH RISK FOR HYPERSENSITIVITY OUR EXPERIENCE - Svarca, Leonora; Bojadzieva, Sonja; Rashiti, Premtim; Rashiti - Bytyci, Albiona (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Vaccines are recognized as one of the most effective public health interventions. Routine immunization has resulted in large reductions in vaccine-preventable disease and death. Vaccine-related hypersensitivity reactions are not uncommon. The concern about the occurrence of hypersensitivity reactions to the vaccine itself or to any component of the vaccine is one of the key obstacles to vaccination. Although this is an uncommon occurrence, it is necessary to establish a reliable approach in order to identify people who are at risk of such suffering. The rapid development and launch of several new COVID-19 vaccines (mRNA and adenovirus vector) is a new experience of modern science. Patients who are considered to be at high risk for allergy and/or have had a previous allergic reaction to the COVID-19 vaccine are usually referred to an allergist for vaccine allergy testing. The aim of this study was to present the allergic reactions with Skin Prick Test and Intradermal Test from the anti Covid 19 vaccines (mRNA and adeno viral vector) at patients with a history of allergy to the first COVID-19 vaccine dose as well as patients with high risk of allergic reaction.  The research was a retrospective cross-sectional study that was conducted between December 2020 and February 2023 at the Clinic for Allergology and Clinical Immunology at the University Clinical Center in Kosovo,. The research included all patients aged â‰¥ 18 years who underwent a test for allergy to the vaccine against COVID-19, namely mRNA (BNT162b2, Pfizer) and/or adeno virus vector (AZD1222, AstraZeneca). Testing for allergy to the vaccine against COVID-19 was done by trained allergists, by applying IDT (intradermal test) or SPT (skin prick test). The study included all patients with an indication for testing for allergy to the Covid-19 vaccine due to a history of hypersensitivity to the first dose of the COVID-19 vaccine and/or due to a high risk of allergic reaction, including a history of atopic allergy or anaphylaxis. Results: SPT and IDT testing for allergic reactions from the mRNA vaccine (BNT162b2, Pfizer) indicated a positive finding in 4 (2.58%) of the patients. All positive findings were obtained from IDT testing. In 1 (0.64%) of the patients there was an IDT (1/100), and in 3 (3.80%) there were IDT (1/10) erythema and papules positive findings. Testing with SPT and IDT for allergic reactions from the vaccine AZD1222, Astra Zeneca indicated that there was a positive finding in 3 (3.80%) of the patients. All positive findings were obtained from IDT testing. One (1.26%) of the patients had IDT (1/100), and 2 (2.53%) had both IDT (1/100) and IDT (1/10) erythema and papulle positive findings. Our data support that cutaneous reactions to COVID-19 vaccination are generally minor and self-limited and should not discourage vaccination. Findings of the effect of SPT and IDT testing in the prediction of allergic reactions from the COVID-19 vaccines, as mRNA (BNT162b2, Pfizer) or adenovirus vector (AZD1222, AstraZeneca), are still very limited and further research are needed. Health care workers must be aware of these potential vaccine reactions and advise patients accordingly. Keywords: COVID-19, vaccine, hypersensitivity; SPT, IDT, mRNA, adeno viral vector.